0066 Glycinergic Postsynaptic Inhibition is Responsible for the Suppression of Hypoglossal Motoneuron Activity During Naturally-Occurring REM Sleep. (27th May 2020) - Tobin, C; Fung, S J; Xi, M; Chase, M H
Abstract: Introduction: The present study was undertaken to explore the role of glycinergic postsynaptic inhibition and monoaminergic disfacilitation (a withdrawal of excitatory noradrenergic and serotonergic inputs) in the control of hypoglossal motoneuron activity during REM sleep. Accordingly, glycinergic, noradrenergic and serotonergic antagonists were microinjected into the hypoglossal nucleus, and their effects on the hypoglossal nerve activity during REM sleep were examined in chronically-instrumented, unanesthetized cats. Methods: Adults cats were prepared for monitoring behavioral states of sleep and wakefulness, and for extracellular recordings from hypoglossal nerve. Strychnine (a glycinergic antagonist) and a mixture of prazosin (a noradrenergic antagonist) and methysergide (a serotonergic antagonist) were microinjected, separately, into the hypoglossal nucleus during naturally-occurring states of sleep and wakefulness. Results: During REM sleep, compared to non-REM sleep, the hypoglossal nerve activity decreased by 17.4±1.5% (n=17) in the control recordings (prior to the injection of strychnine). Following the microinjection of strychnine, there was only a mean decrease of 7.2±1.2% (n=12) in the nerve activity during REM sleep versus NREM sleep. The strychnine effect was statistically significant compared to control (p<0.001; unpaired t-test), which indicates that strychnine blocks REM sleep-related suppression of hypoglossal nerve activity. In contrast, the microinjection of prazosin and methysergide did not significantly reduce the hypoglossal nerve activity during REM sleep (control: 15.9±2.3, n=9 vs. prazosin+methysergide: 12.6±1.4%, n=10, p=0.229, unpaired t-test). Conclusion: The present results demonstrate that the microapplication of strychnine, but not prazosin and methysergide, into the hypoglossal nucleus significantly reduces the suppression of the hypoglossal nerve activity during naturally-occurring REM sleep. We therefore suggest that glycinergic postsynaptic inhibition is primarily responsible for the suppression of hypoglossal motoneuron activity during REM sleep. Support: 5R01NS094062